Droplet impact dynamics on the surface of super-hydrophobic BNNTs stainless steel mesh - Lie Zhang; Yongbao Feng; Liang Li; Shuzhi Li; Bo Yuan; Xiaoxia Han; Zhenxin He (Scientific Reports)
Abstract The ‘gas‒liquid‒solid’ mechanism annealing method was used to create a superhydrophobic boron nitride nanotube (BNNT) stainless steel mesh in a tube furnace at 1250 °C in an NH3 environment. Fe powder was used as a catalyst, and B:B2O3 = 4:1 was used as the raw material. The water droplets on the surface of the superhydrophobic material had a contact angle of approximately 150° and a slide angle of approximately 3°. By using molecular dynamics (MD) simulation technology, a three-dimensional braided physical model of nanodroplets and superhydrophobic BNNT mesh surfaces with the same contact angle and rolling angle was prepared via the function weaving method. The Weber number (We) was used as the entrance point to establish the relationship between macroscale experimental studies and nanoscale MD simulation analysis on the basis of these efforts. A study was conducted on the dynamic behaviour of droplets impacting a superhydrophobic BNNT filter surface. We suggest that the wettability, substrate structure, and impact velocity are connected to the impact dynamic behaviour of droplets on the basis of the data obtained at various scales. The findings demonstrate that when the droplet impact velocity increases, several droplet phenomena—such as impact–rebound, impact–spread–rebound, and impact–spread–breaking–polymerisation–spatter—appear on the substrate surface sequentially. The mechanism of impact behaviour at various scales is explained in light of these events. Furthermore, a better theoretical model is proposed to assess the droplet wetting transition at the nanoscale. This model accurately predicts the boundary Weber number that starts the wetting transition. Moreover, the connections among the impact velocity, spreading diameter, and contact time (or We) are examined. The tendencies found via MD simulations match the outcomes of the experiments. Our discoveries and outcomes broaden our understanding of how droplet impact affects the dynamic behaviour of superhydrophobic surfaces. A scientific foundation for examining the dynamic behaviour of droplets is provided by combining simulations and experiments.